A Novel Chondroitin AC Lyase With Broad Substrate Specificity From Pedobacter rhizosphaerae: Cloning, Expression, and Characterization - Zhou, Li-Jian; Guo, Li-Bin; Wei, Wei; Lv, Zhi-Xiang; Zhang, Ye-Wang (Frontiers in Bioengineering and Biotechnology, 2021)
Chondroitin AC lyase (ChSaseAC) is one of the essential polysaccharides lyases in low molecular chondroitin sulfate production. In this work, a novel PrChSaseAC from Pedobacter rhizosphaerae was successfully cloned, expressed in Escherichia coli. After optimizing the induction, the recombinant PrChSaseAC could be expressed efficiently at 0.1 mM IPTG, 25oC, and 12 h induction. Then it was purified with Ni-NTA affinity chromatography. The characterization of the purified PrChSaseAC showed it had high specific activity and good storage stability, which would favor the production of low molecular weight chondroitin sulfate. It also displayed activity toward chondroitin sulfate C and hyaluronic acid. PrChSaseAC had the highest activity at pH 7.5, 37oC, 10 mM Ca2+, and 5 mg/mL of chondroitin sulfate A. Molecular docking of substrate and enzyme showed the interactions between the enzyme and substrate, it revealed that the enzyme showed high activity to CS-A and HA, but lower activity to CS-C attributed to the structure of the binding pocket. The high stability and specific activity of the enzyme will benefit the industrial production or clinical treatment.